Pengaruh Kinerja Perusahaan, Kepemilikan Institusi, dan Komisaris Independen terhadap Total Kompensasi: Studi pada Perusahaan yang Terdaftar di LQ45 Tahun 2009–2012 - Fitriawan, Rama; Ahmad, Gatot N.; Suherman (Jurnal Aplikasi Manajemen, 2015)
The aim of this study is to determine the effect of the firm performance, institutionalownership, independent commissioner on total compensation controlling for firm size andearnings per share. This research employs multiple regressions with unbalanced panel data.The sample of this study covers 32 companies listed on the LQ45 between 2009 and 2012 (95observations). The results of this study show that the performance of the company as measuredby Return On Equity (ROE) and Net Profit Margin (NPM) significantly affect onexecutive compensation. However, when the firm performance is measured by Return OnAssets (ROA) and Tobin's Q, we find no significant effect on executive compensation. Institutionalownership (INST) and independent directors (IND) have no significant effect onexecutive compensation. Control variables such as earnings per share (EPS) and the firmsize have significant and positive effect on total compensation.